2008
DOI: 10.1016/j.otohns.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Transient and distortion product evoked oto‐acoustic emissions in normal hearing patients with and without tinnitus

Abstract: SG had significantly higher prevalence of abnormal TEOAE and DPOAE than CG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 18 publications
10
43
3
4
Order By: Relevance
“…Abnormal TEOAE results have been reported in 85% of tinnitus patients [21] , and case-control studies comparing patients with and without tinnitus found that abnormalities on TEOAE and DPOAE were significantly more frequent in patients with than without tinnitus [10] . DPOAE has also been associated with hearing loss [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal TEOAE results have been reported in 85% of tinnitus patients [21] , and case-control studies comparing patients with and without tinnitus found that abnormalities on TEOAE and DPOAE were significantly more frequent in patients with than without tinnitus [10] . DPOAE has also been associated with hearing loss [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Six items on the ABR were measured: I latency, III latency, V latency, I-III IPL (interpeak latency), III-V IPL, and I-V IPL [9] . DPOAE and TEOAE were also performed to determine the function of outer hair cells [10] . DPOAEs were categorized based on responses to 1, 2, 3, 4, and 6 kHz, and response or non-response at each pitch was recorded.…”
Section: Tinnitogrammentioning
confidence: 99%
“…Granjeiro et al 30 tested the hypothesis that tinnitus begins with OHC dysfunction by recording DPOAE in 32 tinnitus patients with normal hearing and 37 patients without tinnitus but similar thresholds. In this paper DPOAE were anomalous in 68.4% of the tinnitus patients and in 50% of the healthy ones, showing that the study group had significantly higher prevalence of abnormal DPOAE than the control one.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported increased DPOAE amplitude 33,34 but again, the involved subjects in these studies presented differences in the hearing thresholds, what does not clarify if the irregularities in DPOAE are due to the expansion of tinnitus or due to the hearing losses 32 . Until now, a few studies have investigated DPOAE by including tinnitus patients with normal audiometric thresholds 9,22,29,[30][31][32] . Quite different results were found by Gouveris et al 33 who compared the cochlear OHC function by DPOAE-grams of 32 ears with acute tonal tinnitus and normal hearing or minimal hearing loss with 17 healthy nontinnitus ears.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, researchers have found a significantly higher prevalence of absent or abnormal TEOAEs and DPOAEs in tinnitus patients with normal hearing thresholds (e.g., Sirimanna et al, 1996;Shiomi et al, 1997;Ozimek et al, 2006;Ami et al, 2008;Paglialonga et al, 2010;Granjeiro et al, 2008;Zhou et al, 2011). For example, Granjeiro et al (2008) investigated the prevalence of TEOAE and DPOAE test results in tinnitus patients with and without hearing loss.…”
Section: Insert Figures 4a and 4b Near Here Insert Figure 5 Near Herementioning
confidence: 99%